Poet, poetry and gift of creativity in Marina Tsvetaeva's poetic world - M.V. Tsvetkova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The aim of this paper is to examine Marina Tsvetaeva's view of poet, poetry, and creativity. The novelty of the approach to the subject rests on singling out the key symbolic images and motifs which constitute the representation of the theme in question via “close reading” of M. Tsvetaeva's work and describing their functioning as a system. The approach allows to discover the specifics of interpretation of creativity by the poetess. The motif of an artist as a chosen one turns out to be the key one. The gift of creativity is related in M. Tsvetaeva's poetic universe with personified images of natural forces, Insomnia, Genius, Angel and Demon, which all manifest an ambivalence of the creative process and depict it as an “obsession”. The traditional images of lyre, Muse, gift of singing acquire non-trivial connotations in M. Tsvetaeva's work. The motifs associated with the idea of creativity show that M. Tsvetaeva considers the poetic gift as an ability of “clear hearing” and “dreaming”, “fatal blessing” and “mysterious heat” (a simultaneous metaphor for the creative act and passion). The poet is viewed in M. Tsvetaeva's artistic world as follows: heathen and warlock, seducer and seduced, sinner and saint, and also martyr doomed to drudge and rejected by the philistine crowd.